Perbaikan Rubber Skirt Mesin Belt Conveyor di PT. Cemindo Gemilang Tbk. Analisis Potensi Bahaya dan Pengendaliannya - Mardiah, Jamilah; Ikhsanudin, Ikhsanudin (Motor Bakar : Jurnal Teknik Mesin, 2025)
In a job there must be something called work accidents, these work accidents can be caused by humans and the environment, where this is due to unsafe behavior and unsafe conditions. Occupational Health and Safety (K3) is something that is very important and must be given great attention in companies/industry in the current era. From the research conducted, it aims to carry out an analysis of the potential hazards and how to control the Conveyor Belt Machine. This research was conducted using a descriptive method, which was to obtain data through literature studies and documentation. The data were combined from industry, journals and the internet. Belt Conveyor is one of the equipment in the cement company PT. Cemindo Gemilang Tbk. Belt Conveyor as a machine for moving and transferring material along a horizontal direction or with a continuous slope. In general, the potential for danger at PT. Cemindo Gemilang Tbk. has been identified and handled well. To improve health and safety at work, various identified potential hazards can become knowledge for implementing work more thoroughly and carefully.Keywords: control, conveyor belt, K3, potential hazard.Dalam sebuah pekerjaan pasti ada yang namanya kecelakaan kerja, dari kecelakaan kerja ini bisa disebabkan oleh manusia dan lingkungan, dimana hal ini karena perilaku tidak aman dan kondisi tidak aman. Keselamatan dan Kesehatan Kerja (K3) adalah sesuatu yang sangat penting dan harus sangat diperhatikan di dalam perusahaan/industri di era saat ini. Dari penelitian yang dilakukan bertujuan untuk melakukan analisis pada potensi bahaya dan cara pengendalian terhadap Mesin Belt Conveyor. Penelitian yang dilakukan ini adalah menggunakan metode deskriptif, yang mana untuk mendapatkan data melalui studi pustaka, studi literatur, informasi-informasi atau data dari industri, jurnal maupun internet. Belt Conveyor merupakan salah satu equipment yang berada di perusahaan semen PT. Cemindo Gemilang Tbk. Belt Conveyor sebagai mesin untuk memindahkan dan mentransfer material dengan sepanjang arah yang horizontal atau dengan kemiringan secara continue (terus menerus).Kata kunci: potensi bahaya, pengendalian, k3, belt conveyor.